2006
DOI: 10.1681/asn.2006030275
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Kidney-Derived Stem Cells

Abstract: Acute kidney injury is followed by regeneration of damaged renal tubular epithelial cells. The purpose of this study was to test the hypothesis that renal stem cells exist in the adult kidney and participate in the repair process. A unique population of cells that behave in a manner that is consistent with a renal stem cell were isolated from rat kidneys and were termed multipotent renal progenitor cells (MRPC). Features of these cells include spindle-shaped morphology; self-renewal for >200 population doublin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
194
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(203 citation statements)
references
References 37 publications
4
194
0
5
Order By: Relevance
“…The renal papilla has been proposed as a niche area, based on the distribution of BrdU-labelled cells after a period of postnatal labelling in rodents, but the frequency of LRCs (40%) was far too high for them all to be stem cells [150]: nevertheless, LRCs disappeared after ischaemic injury and displayed clonal growth in vitro. Cells expressing Pax-2 and vimentin, with extensive clonogenic capacity in vitro and tubulogenic capacity in vivo, have been isolated from rat kidney; in one case they were CK-negative [151] and in another study came from the proximal tubule S3 segment [152].…”
Section: Kidneymentioning
confidence: 99%
“…The renal papilla has been proposed as a niche area, based on the distribution of BrdU-labelled cells after a period of postnatal labelling in rodents, but the frequency of LRCs (40%) was far too high for them all to be stem cells [150]: nevertheless, LRCs disappeared after ischaemic injury and displayed clonal growth in vitro. Cells expressing Pax-2 and vimentin, with extensive clonogenic capacity in vitro and tubulogenic capacity in vivo, have been isolated from rat kidney; in one case they were CK-negative [151] and in another study came from the proximal tubule S3 segment [152].…”
Section: Kidneymentioning
confidence: 99%
“…Of note, in the heart Camargo et al [37] have [39] Glycerol-induced ARF (mouse) MSCs Enhanced tubular proliferation [68] IR (rat) Papilla LRCs Proliferation and incorporation [149] IR (mouse) Bone marrow No functional improvement, intrarenal cells are the main source of repopulating cell during repair [22] Folic acid-induced acute tubular injury (mouse) Bone marrow Intrinsic tubular cell proliferation accounts for repair after damage [150] Folic acid-induced acute tubular injury (mouse) Bone marrow 10% incorporation in tubules and G-CSF doubles this rate [151] IR (rat) MSCs Improved renal function and less injury [152] Cisplatin-induced renal failure (mouse) MSCs Accelerated tubular proliferation [153] UUO (mouse) Bone marrow macrophages Reduced renal fibrosis [41] IR (rat) MSCs Improved renal function, increased proliferation and decreased apoptosis [84] IR (rat) rKS56 (S3 segment outgrowth) Replace tubular and improve function [80] Glycerol-induced tubulonecrosis (mouse) Human CD133 + cells Homing and tubular integration [66] UUO (rat) Label-retaining cells (LRC) Proliferates, migrates and transdifferentiates into fibroblast-like cells [27] Cisplatin-induced renal failure (mouse) G-CSF ± M-CSF Improvement in renal function and prevention of renal tubular injury [154] Anti-Thy1.1 GN (rat) MSCs Increased glomerular proliferation and reduction in proteinuria [53] Col4α3 deficiency (mouse) MSCs Prevented loss of peritubular capillaries and reduced fibrosis but no increase in function or survival [24] Col4α3 deficiency (mouse) Bone marrow Partial restoration of expression of the type IV collagen α3 chain, improved histology and function [25] Col4α3 deficiency (mouse) MSCs Improved function and glomerular scarring and interstitial fibrosis reduced [155] UUO (mouse) BM Instertitial BM-derived cells do not contribute significantly to collagen synthesis after damage [74] Adriamycin-nephropathy (mouse) Renal side population Functional amprovement but very low rate of engraftment. [78] IR (rat) Multipotent renal progenitor cells In vivo epithelial differentiation, no difference on renal function [67] Cultured metanephroi (rat) LRCs Integration [81] Glycerol injection (mouse) Human CD24 + CD133+ Tubular regeneration and function improvement [83] IR (mouse) Mice Sca-1 + cells Adopt tubular phenotype …”
Section: Bone Marrow-derived Cellsmentioning
confidence: 99%
“…Gupta et al [78] attempted to use specific culture conditions to preferentially isolate cell populations possessing stem cell characters. Multipotent renal progenitor cells (MRPC) were isolated by culturing dissociated adult rat kidney in a defined low serum medium with supplements [78].…”
Section: Progenitors Isolated Based Upon Cellular Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…37 In addition, a number of studies seeking evidence for postnatal renal stem/progenitor cells have identified non-tubular mesenchymal populations with limited or no tubular potential that may represent such a population. [38][39][40] Outside of the kidney, there is growing evidence that MSC populations frequently exist within the perivasculature where they can express pericyte markers. 41 ( Fig.…”
Section: The "Niche" In the Kidney During Development And Adult Lifementioning
confidence: 99%